Dual Modality Acupressure and Thermotherapy for Menstrual Pain Mitigation in Junior High Students: Terapi Akupresur dan Termoterapi Ganda untuk Meredakan Nyeri Haid pada Siswa Sekolah Menengah Pertama - Evi Rinata; Vindiah Dwi W (Indonesian Journal on Health Science and Medicine, 2026)
General Background Dysmenorrhea represents a highly prevalent gynecological condition among adolescent females globally, commonly driven by progesterone imbalances that induce painful uterine cramps. Specific Background Secondary school students frequently experience severe menstrual pain that interferes with daily school attendance and regular academic performance. Knowledge Gap Although separate non-pharmacological methods exist, the comparative performance of combined reflexology and thermal protocols remains under-explored in localized school environments. Aims This study evaluates the management of dysmenorrhea using integrated acupressure at SP6 and LV3 points alongside warm compresses among junior high respondents. Results Quantitative analysis of 33 participants revealed that combined therapy significantly decreased visual analogue scale scores ($p = 0.000$) compared to single acupressure or control groups. Novelty The evaluation demonstrates that dual-modality alternative care yields a more substantial physiological decline in pain intensity than isolated acupressure interventions. Implications School health services should adopt integrated non-pharmacological interventions as safe, accessible alternatives to conventional analgesic medications. Keyword: Sdysmenorrhea, Acupressure, Warm Compresses, Menstrual Pain, Adolescent Health Key Findings Highlights Visual analogue scale records reveal optimal pain reduction when combining meridian stimulation with deep tissue thermotherapy. Isolated acupressure targeting specific regional channels induces secondary relief compared to multi-modality approaches. Untreated control groups demonstrate an upward trajectory in menstrual distress during active observation cycles.